A bibliometric analysis of cultural and creative industries in the field of arts and humanities. Issue 4 (2nd October 2021) - Bui Hoai, Son; Hoang Thi, Binh; Nguyen Lan, Phuong; Tran, Trung
ABSTRACT: The development and main characteristics of global research related to cultural and creative industries from 1995 to 2020 have been investigated using bibliographic data derived from the Scopus database. We identified 746 single-authored documents among a total of 1099 documents indexed in the Scopus database during this period, with an annual growth rate of 18%. English-speaking countries such as the UK, the USA, Australia and Canada were the most important contributors to this research field, participated in more than 50% of documents of the collection. The most productive scholars and institutions were all located in Australia and the UK. Quality of the publication collection was good, as nine over ten most popular journals who published a quarter of the collection, were classified into the first quartile of the SCImago Journal & Country Rank. Cultural policy and creative economy were the most important research directions of the collection.